Theoretical & Experimental Studies on Vibration & Damping of Fibre-Reinforced Cantilever Laminates. - Ganapathi, M.; Patel, B.P.; Kemkar, K. (Defence Science Journal, 2013)
In this paper, vibration and damping analyses of glass fibre-reinforced laminated composite cantilever beams and plates are studied using C1 finite element using shear deformation theory and alsothrough experiments. The formulation in the theoretical model includes in-plane and rotary inertiaterms. The governing equations for the complex eigenvalue problem based on complex elastic moduliare formulated. The solutions are obtained using QR algorithm. Parametric study is carried out tohighlight; the effects of lay-up and ply-angle of the laminates. A limited number of experimentalinvestigafions on cantilever laminates are conducted for obtaining the natural frequenciqs, dampingfactor and frequency responses. The comparison between the theoretical and the experimfntal resultsshows good agreement.